Impact of cardiac resynchronisation therapy in patients with cardiac sarcoidosis. (3rd October 2022) - Ahmed, R; Shi, R; Pan, J; Okafor, J; Azzu, A; Qadeer, A; Khattar, R; Baksi, J; Wechalekar, K; Wells, A; Kouranos, V; Sharma, R
Abstract: Background: Implantation of a device is usually required in cardiac sarcoidosis (CS) patients presenting with advanced conduction abnormalities or ventricular arrhythmias. A cardiac resynchronisation therapy (CRT) device is often chosen in patients with concomitant left ventricular systolic impairment. The role of CRT in CS is not well established. Purpose: To describe the cohort of CS patients with CRT device in situ in our hospital focusing on the short-term effect in serial echocardiography and long-term outcomes on morbidity and mortality. Methods: All consecutive CS patients with a CRT device in situ were identified in our CS database (2005–2022). A confident CS diagnosis was provided after review of all relevant clinical and imaging baseline data in our CS multi-disciplinary meeting and a consensus decision for CRT-D implantation was made based on international guidelines. All patients were followed up for at least 6 months with serial echocardiography. Serial data regarding symptoms, rhythm disturbance and echocardiographic parameters were obtained and comparisons were performed using Wilcoxon signed rank test. Results: A total of 51 CS patients with CRT-D were identified (mean age: 57±10 years old). Patients were male predominant (64.7%) and Caucasian in origin (86.2%). Extra-cardiac sarcoidosis was confirmed histologically in 33 (64.7%) patients. The prevalence of smoking, diabetes, hypertension and ischaemic heart disease was 27.5%, 21.6%, 49.0% and 7.8% respectively. At the time of device implantation or during follow-up, 43 (84.3%) patients were found to have active cardiac sarcoidosis on cardiac PET. Post CRT implantation there was a significant difference in LV ejection fraction (35.9±15.0% vs 42.2±14.1%, p<0.001), LV end-systolic diameter (4.90±1.46 cm vs 4.62±1.32 cm, p=0.012) and LV end-diastolic diameter (5.99±1.18 cm vs 5.66±1.06 cm, p<0.001). No significant changes were observed in the right ventricular function (p=0.09) and severity of mitral regurgitation (p=0.40). There was one patient who experienced acute heart failure decompensation admission within six months of CRT-D implantation. The New York Heart Association (NYHA) class improved in 26 patients (51.0%), worsened in 4 (7.8%) patients and remained the same in 21 (41.2%) patients at 6 months post CRT-implantation. During the mean follow up of 47.6 months, the composite end-point of death and cardiac transplantation was reached in 9 (17.6%) patients (8 deaths and 1 cardiac transplantation). 5 patients had major complications including a large haematoma, a small atrio-septal defect, haemothorax, device associated endocarditis and lead fracture. Minor wound infections were seen in 3 patients and 4 patients received inappropriate shock or anti-tachycardia pacing. Conclusions: CRT in cardiac sarcoidosis patients is associated with short-term improvement in LV remodelling and functional status but over a four year follow up, morbidity and mortality are common. Funding Acknowledgement: Type of funding sources: None.